The Impact of Social Media Marketing Activities and Brand Ambassadors on University Purchase Decision: The Case of Unisa Yogyakarta’s TikTok Campaigns - Rizali Zaka Wali; Fitri Maulidah Rahmawati (Menulis: Jurnal Penelitian Nusantara, 2025)
This study aims to examine the influence of Social Media Marketing Activities (SMMA) and brand ambassadors on brand equity, as well as how these variables directly and indirectly affect purchase decision at Universitas ‘Aisyiyah Yogyakarta (UNISA). The study focuses on UNISA’s TikTok campaigns, which serve as the primary platform for digital marketing and brand ambassador engagement. Respondents in this study were active students of UNISA from the 2023/2024 and 2024/2025 academic years who actively use TikTok. A total of 321 valid responses were collected through an online questionnaire. The research employed multiple linear regression and PROCESS Macro analysis using SPSS version 27 to test the hypotheses. The findings reveal that both SMMA and brand ambassadors have a significant positive effect on brand equity and purchase decision. Brand equity also significantly affects purchase decision. However, SMMA and brand ambassadors do not have an indirect effect on purchase decision through brand equity.